(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2004)
For a graph G the symbol G→(4,4) means that in every 2-coloring of the vertices of G there exists a monochromatic K_4. For the vertex Folkman number \[ F(4,4;5)={|V(G)| : G→(4,4) and K_5 otG} \] we show that 16F(4,4;5)35.